Development of Tax Avoidance Research in Asia through Bibliometric Analysis - Loso Judijanto (Westscience Press, 2024)
This research employs a bibliometric analysis to investigate the development and trends in tax avoidance research, focusing specifically on the Asian context. Utilizing data from Google Scholar, the study covers literature published between 1938 and 2024. The analysis identifies key thematic clusters including corporate tax avoidance, international tax strategies, and legal frameworks, highlighting the evolution of research focus from foundational legal issues to complex multinational tax practices and ethical considerations. The study also uncovers underexplored areas such as the incentives driving tax avoidance behavior and the role of audit committees, presenting opportunities for future research. Furthermore, the author collaboration network reveals a landscape with significant yet underutilized potential for interdisciplinary cooperation. This comprehensive overview not only enhances understanding of the tax avoidance research landscape but also underscores the need for continued scholarly exploration and collaboration to address emerging challenges in the field.